A 90 g/day low‐carbohydrate diet improved glycemic control without decreasing frailty in older patients with type 2 diabetes: A secondary analysis of a randomized controlled trial - Yu‐Ting Wang; Chin‐Ying Chen; Wei‐Sheng Huang; Hui‐Chuen Chen; Long‐Teng Lee; Chyi‐Feng Jan; Hsien‐Liang Huang; Jaw‐Shiun Tsai (Journal of Diabetes Investigation)
ABSTRACT Aims This study explored the glycemic control and Fried frailty criteria of a 90 g/day low‐carbohydrate diet (LCD) in older patients with type 2 diabetes over 18 months. Methods Forty‐four older patients with type 2 diabetes and HbA1c ≥ 7.5% (58 mmol/mol) at the outpatient clinics were randomly assigned to a 90 g/day LCD or traditional diabetic diet (TDD). The analysis was performed using an intention‐to‐treat analysis. Results A total of 42 (95.5%) patients completed the trial. The 18‐month mean change from baseline was statistically significant for 2‐h glucose (−100.0 ± 57.7 vs −18.6 ± 86.2 mg/dL) and waist circumference (−6.3 ± 7.9 vs −1.7 ± 4.7 cm) between the LCD and TDD groups (P < 0.05). The 18‐month mean change from baseline was not significantly different in HbA1c (−1.55 ± 1.0 vs −0.97 ± 1.2; P = 0.097). After intervention, the proportions of robust, pre‐frailty, and frailty in the TDD and LCD groups were 20.0% vs 13.6%, 75.0% vs 86.4%, and 5.0% vs 0.0%, respectively (P > 0.05). Conclusions A 90 g/d LCD reflected improved glycemic control with significantly lower waist circumference without decreasing frailty in older patients with type 2 diabetes.